A NEW ERA FOR LIBERAL ARTS: GLOBAL CHANGES AND EMERGING POSSIBILITIES - Malcolm, Matthew R (PEOPLE: International Journal of Social Sciences, 2018)
This article explores the changes and possibilities for liberal arts education in what has been called the ‘Asian Century.’ The article represents conceptual research, in that it attempts to offer interpretative and speculative commentary on the state of liberal arts at this time, from the perspective of the Dean of a Faculty of Liberal Arts in an Asian University. At the same time, the article draws on empirical research, including recently published research by the author on the nature of liberal arts in South-East Asia.Following a survey of this and other relevant literature, it is proposed that liberal arts faces certain changes at this point of time, which may present opportunities for reinvigoration of the educational approach. These include: the pressures toward economic or utilitarian motivations for education; the evolving places of science and humanities in a general education curriculum; and the controversial place of religion and theology in liberal arts education.While each of these issues presents challenges, it is possible to regard this period of contestation as providing an opportunity for this classic educational approach to find fresh relevance.